INFORMACIÓN TELEVISIVA Y MOVILIDAD. ANÁLISIS DE LAS NOTICIAS MÁS SEGUIDAS A TRAVÉS DE TWITTER - Dra. Leire GÓMEZ RUBIO,Dra. Nereida LÓPEZ VIDALES (Fonseca, Journal of Communication, 2023)
Social networks such as Facebook and Twitter, and mobile applications such as Periscope, Snapchat, Whatsapp, among others, are some of the emerging ways of communication and access to information in recent times, for both general users and professionals of the information. Technological advances and innovations derived mainly from the web 2.0 have added new screens to traditional media, so that the newspaper can not only be read, but now also can be seen and heard, while television, besides been seen and heard, also read.